1997
DOI: 10.1093/emboj/16.18.5697
|View full text |Cite
|
Sign up to set email alerts
|

A mutation mimicking ligand-induced conformational change yields a constitutive RXR that senses allosteric effects in heterodimers

Abstract: Mutations of a single residue in the retinoid X receptor α (RXRα) ligand‐binding pocket (LBP) generate constitutive, ligand‐binding‐competent mutants with structural and functional characteristics similar to those of agonist‐bound wild‐type RXR. Modelling of the mouse RXRαF318A LBP suggests that, like agonist binding, the mutation disrupts a cluster of van der Waals interactions that maintains helix H11 in the apo‐receptor location, thereby shifting the thermodynamic equilibrium to the holo form. Heterodimeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
0
3

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 61 publications
7
95
0
3
Order By: Relevance
“…9cRA is a ligand for RXR, and the PPAR␥-RXR and LXR-RXR heterodimers are know to retain ligand-dependent activation of RXR together with specific PPAR␥ or LXR activation (10,24,(53)(54)(55)(56). It is possible that 9cRA act in DCs via the RXR moiety of PPAR␥-RXR, or LXR-RXR heterodimers (57)(58)(59) or even by activation of RXR homodimers (which have recently been described to be able to bind to functional PPAR response elements) (22,60).…”
Section: Discussionmentioning
confidence: 99%
“…9cRA is a ligand for RXR, and the PPAR␥-RXR and LXR-RXR heterodimers are know to retain ligand-dependent activation of RXR together with specific PPAR␥ or LXR activation (10,24,(53)(54)(55)(56). It is possible that 9cRA act in DCs via the RXR moiety of PPAR␥-RXR, or LXR-RXR heterodimers (57)(58)(59) or even by activation of RXR homodimers (which have recently been described to be able to bind to functional PPAR response elements) (22,60).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that 9-cis RA strongly enhances the transcriptional activity of the NGFI-B/RXR heterodimer in vitro ( Nuclear receptors and neuroleptic effects I Éthier et al Vivat et al, 1997). More recently, DHA has been identified as a natural ligand for retinoid receptors (de Urquiza et al, 2000;Egea et al, 2002).…”
Section: Retinoid Ligands Can Suppress Haloperidol-induced Catalepsymentioning
confidence: 99%
“…Based on these considerations, it is tempting to suggest that both NGFI-B and RXR, possibly as a transcriptional complex, may be involved in the signaling cascade induced by haloperidol. Indeed, it has been shown that NGFI-B and RXR can form an heterodimer that is active on transcription (Vivat et al, 1997;Castillo et al, 1998) and that 9-cis RA strongly enhances the transcriptional activity of the NGFI-B/RXR heterodimer in vitro (Heyman et al, 1992;Vivat et al, 1997). The acute effect of retinoid ligands on haloperidolinduced catalepsy may be too rapid to support an alteration of retinoid receptor-dependent transcriptional activities.…”
Section: Ngfi-b(+/+) Ngfi-b(-/-) Ngfi-b(+/+) Ngfi-b(-/mentioning
confidence: 99%
See 1 more Smart Citation
“…Among the three genes (Nur77, Nurr1, and NOR1) which constitute the NR4A nuclear receptor family, Nur77 and Nurr1 have similar molecular biological characteristics, in that both receptors function as transcription factors forming heterodimers with retinoic X receptor (RXR) (Perlmann and Jansson 1995;Zetterstrom et al 1996a;Vivat et al 1997;Maira et al 1999). They can mediate efficient transactivation through a DR-5 element in response to the RXRspecific ligand, 9-cis retinoic acid.…”
Section: Apoptotic Characteristics Of the Nr4a Nuclear Receptormentioning
confidence: 99%